THE USE OF SUPPLEMENTS WHEY PROTEIN BCAA IN ADULTS AND PRACTITIONERS OF STRENGTH IN AN ACADEMY OF BELÉM – PA. (Fiep Bulletin - online, 2012)
Concern about the quality of life emphasized the importance of nutrition for exercise, changing eating habits and life in people of all ages. The use of nutritional supplements protein is widespread among bodybuilders in gyms in order to achieve immediate results, especially muscle hypertrophy. However, its use is not well quantified, and there is little information in scientific literature. Consequently, the indiscriminate use has gradually increased without adequate knowledge of the benefits and harms that such supplements can cause human health. Objectives: To assess the consumption of supplements whey and BCAA protein by adults aged 18 to 59 years who practice bodybuilding and correlate the alert with the aim of verifying the use and display them. Methods: We performed a cross-sectional survey, data were collected from 20 individuals of both sexes who do weight training at a gym in Bethlehem, in the period from April to May 2011. The analysis of data collected was done from the software Microsoft Excel 2010 through. Results: We found that 95% of 20 respondents were male, 60% with college degrees, 60% use whey protein with the goal of hypertrophy associated with improved performance and compensate for deficiencies in power, and its main objective is hypertrophy. Since BCAA 57.1% said use with the goal of hypertrophy, but there are no studies that prove this fact. Conclusion: Considering the results and analyzed studies on the subject, we can say that the population research has mainly aimed at muscle hypertrophy, but not sure about the need for such supplementation, making ingestion under the influence of professionals trained not to indicate the same.
Keywords: Supplements; whey protein; BCAA.